ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI DENGAN METODE HARGA POKOK PROSES (Studi Kasus pada Usaha Kasur Ibu Nunung Kabupaten Karawang) - Rahmah Novia; Nisa Fuji Budiarti; Maulida Naba Samawati (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2022)
This study aims to understand and find out how to calculate the cost of production using the process costing method in the mattress business of Mrs. Nunung in the Karawang district. The method used in this research is a case study by making direct observations to the place of business and conducting interviews with the business owner, Mrs. Nunung. The results of the research that the researcher has done show that the production costs that arise in the September 2021 period are Rp. 62,3766,000 consisting of raw material costs of Rp. 55,016,000, the cost of auxiliary materials of Rp. 2,180,000, labor costs of Rp. 4,680,000 and factory overhead costs of Rp. IDR 500,000. The production cost added to each unit of mattress is Rp.121,061. So that there is a difference in calculations between the calculations of researchers and calculations according to Nunung's mother of Rp. 3,939. The total income of Mrs. Nunung's Mattress Business in September 2021 is Rp. 78,000,000.